Archetypal Construction of Major Female Characters in the Works of Three Nigerian Novelists - Ibanga, Grace Itoro (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The purpose of this essay is to examine the archetypal construction of female characters in the works of three Nigerian novelists. It explores Adimora-Ezeigbo’s, Emecheta’s and Adichie’s portrayal of women in their maternal, spiritual, educative, domestic and productive capacities (or locations), in an exclusive patriarchal society, using Jungian model. The study argues that through the protagonists display of archetypal Mothers’ perfections and innocent youth, the novelists use womanhood to project definitely positive images of healthy nations and humanity. It posits that Jung’s position that universal images had existed since the remotest times, are more or less hidden somewhere in our biological, psychological and social natures. It concludes that the views of archetypes as collective unconscious are capable of being applied in all human endeavours in the real world. Key words: Archetypes, universal images, Jungian collective, unconscious, archetypal Mother, maternal, spiritual locations.